1969
DOI: 10.1136/hrt.31.4.462
|View full text |Cite
|
Sign up to set email alerts
|

Q-second sound interval in acute myocardial infarction.

Abstract: In clinical practice an objective measurement of cardiac function is desirable in following patients with acute myocardial infarction. Jegek (1963) and Weissler, Harris, and Schoenfeld (1968) have suggested that the Q-S2 time interval expressed as a fraction of the cardiac cycle length may be of value in the assessment of cardiac function. We have measured this interval in a series of normal patients and in those who have had a myocardial infarction. The purpose of this paper is to evaluate the practical va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
3

Year Published

1971
1971
1994
1994

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 7 publications
(5 reference statements)
1
3
0
3
Order By: Relevance
“…On the 21st day the values were approximately the same as on the 1st day. These findings are in agreement with several other studies (1, 3, 4, 6, 8, 10, I I , 13,14,15,16). QS2 and especially LVET have been found to be correlated to stroke volume (6).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…On the 21st day the values were approximately the same as on the 1st day. These findings are in agreement with several other studies (1, 3, 4, 6, 8, 10, I I , 13,14,15,16). QS2 and especially LVET have been found to be correlated to stroke volume (6).…”
Section: Discussionsupporting
confidence: 94%
“…In our patients with AMI, we found a strong correlation between LVET and HBDH serum levels. Another study has shown good correlation between QS2 and the LDH level in serum (14). The rise in HBDH has been shown to be in direct relationship to the development of heart failure and cardiogenic shock (2).…”
Section: Lvetoi Pep10mentioning
confidence: 99%
See 1 more Smart Citation
“…The indices determined using these methods are primarily measures of left ventricular performance (Weissler et al, 1969;Lewis et al, 1976). Though STI have limited use in differential diagnosis, they serve to quantify the effects on the cardiovascular system of various pharmacological interventions (Harris et al, 1966(Harris et al, , 1967 or disease states (Weissler et al, 1968;Toutouzas et al, 1969;Lewis et al, 1976), as multiple observations in the same individual are possible.…”
Section: Discussionmentioning
confidence: 99%
“…Εις τους ασθενείς εκείνους, ο'ΐτινες εμφανίζουν ήλαττωμένην καρδιακήν παροχήν, ό βαθμός τών μεταβολών του χρόνου εξωθήσεως και τής προεξωθητικής περιόδου τής αριστεράς κοιλίας είναι ανάλογος προς τον βαθμόν ελαττώσεως τοϋ όγκου παλμοΰ και τής καρδιακής παροχής. Έπί μικράς ελαττώσεως τής καρδιακής παροχής και τοϋ όγκου παλμού αί πΐχρατηρούμεναι μεταβολαί τών ώς άνω δύο χρονικών φάσεων τοϋ καρδιακού κύκλου είναι μικρού βαθμού, ενώ επί σοβαράς πτώσεως τής παροχής και τοϋ όγκου παλμοΰ αύται είναι έκσεσημασμέναι 55 , 56 .…”
Section: αίμοδυναμικαί μεταβολαί επί χρόνιου πλήρους κολποκοιλιακού αποκλεισμούunclassified